Darriwilian bryozoans from the San Juan Formation (Ordovician), Argentine Precordillera (Ameghiniana, 2010)
A detailed study is carried out on the taxonomy of the bryozoan fauna from the upper levels of the San Juan Formation (Darriwilian) in the Talacasto and Cerro Viejo sections, Argentinean Precordillera. Three bryozoan genera are described and two new species are erected: Lamottopora multispinosa sp. nov., Aostipora sanjuanensis sp. nov., and Phylloporinidae sp. indet. The paleoecological significance of the bryozoan fauna is discussed. The ramose bryozoans Lamottopora and Aostipora dominate in the Talacasto section. Some colonies probably lived attached directly to the substrate, while others occur attached to the surface of the abundant sponge fauna in the section. The majority of bryozoans at the Cerro Viejo section occur as epibionts, with bases attached to the surface of sponges. Bryozoans collected in the matrix are scarce compared to the Talacasto section, and comprise a few fragments of ramose bryozoans and two small fragments of the reticulate Phylloporinidae sp. indet were recorded exclusively in this locality. The presence of this delicate form in Cerro Viejo is further evidence of the quiet water conditions suggested for these levels. Only the laminar form Nicholsonella occurs in slightly older levels (Floian) of the San Juan Formation. The low diversity recorded here shows a slight decoupling with the global pattern. The first local radiation (three genera) is minor compared with the important radiation that the phylum experienced elsewhere. BRIOZOOS DARRIWILIANOS DE LA FORMACIÓN SAN JUAN (ORDOVÍCICO) DE LA PRECORDILLERA ARGENTINA. Se ha realizado un estudio taxonómico detallado de la fauna de briozoos de los niveles superiores (Darriwiliano) de la Formación San Juan en las secciones de Talacasto y Cerro Viejo, Precordillera Argentina. Se describen tres géneros y se definen dos nuevas especies: Lamottopora multispinosa sp. nov., Aostipora sanjuanensis sp. nov. y Phylloporinidae sp. indet. Se discute el significado paleoecológico de la fauna de briozoos. Los briozoos ramosos como Lamottopora y Aoistopora dominan en la sección de Talacasto. Algunas colonias vivieron fijadas directamente sobre el sustrato, aunque también aparecen como epibiontes sobre la superficie de esponjas, que son muy abundantes en este intervalo. En la sección de Cerro Viejo los briozoos se encuentran mayoritariamente adheridos a la superficie de las esponjas, mientras que algunos fragmentos de briozoos ramosos, incluyendo dos colonias del briozoo reticulado Phylloporinidae sp. indet, aparecen en el sedimento. La presencia de estas formas delicadas en el Cerro Viejo es una nueva evidencia de la baja energía del agua como fue sugerido para estos niveles. En las calizas de la Formación San Juan sólo el género laminar Nicholsonella aparece en niveles algo más antiguos (Floiano). Esta baja diversidad muestra un desajuste con las curvas globales de diversidad del grupo. La primera radiación local (géneros), descripta en esta contribución, es también significativamente menor y muestra un desacople con la diversificación que experimenta el grupo para este mismo intervalo temporal en otras regiones